Medical memories and experiences in Postwar East Germany : treatments of the past - Wahl, Markus ([Place of publication not identified] : Routledge, 2019)
This book draws on the example of the major cities of Leipzig and Dresden to illustrate continuity and change in public health in the German Democratic Republic. Based on archival work, it will demonstrate how members of the medical profession successfully manipulated their pre-1945 past in order to continue practising, leading to persistence in the social conception of medicine and disease after Communism took hold. This was particularly evident in attitudes towards and treatment of sexually transmitted diseases and the pathology of deviant behaviour among young people.
List of Figures List of Tables Acknowledgements Abbreviations Introduction: Medical Memories and Experiences Chapter 1 Treating the Past: Narratives of the Medical Profession after 1945 Chapter 2 Treatments from the Past: Continuities in Treating Venereal Diseases Chapter 3 Treatments for the Past? 'War Children' and the New State Chapter 4 Institutionalised Treatments of the Past: The Fürsorgeheim Leuben in Postwar Dresden Epilogue Appendix Index
OCLC-licensed vendor bibliographic record.
Keywords: Medicine -- Germany -- History -- 20th century